The Effect of CSR Practices on Employee Affective Commitment in the Airline Industry. Issue 3 (1st October 2016) - Kucukusta, Deniz; Denizci Guillet, Basak; Chan, Ho Ling
ABSTRACT: This study investigates the corporate social responsibility (CSR) practices of airlines and their influence on the affective commitment (AC) of their employees. The CSR practices were derived from medium-scale airlines in Hong Kong, their annual sustainability reports, and the previous literature. The CSR practices were factor analyzed and grouped under the dimensions of safety, the community, people, the environment, and business operations. While all five dimensions were relevant, employees considered the environmental dimension to be the most important. The dimensions of environment and people were found to have the most influence on employee AC.